Einstein-nonlinear Maxwell-Yukawa black hole - Mazharimousavi, S. Habib; Halilsoy, Mustafa (World Scientific Publ Co Pte Ltd, 2019)
Within the context of nonlinear electromagnetism, we consider the Yukawa extension of a Reissner-Nordstrom black hole. Exact solution is given which modifies certain characteristics of the latter. Some thermodynamical aspects are given for comparison. The model which is based on a nonpolynomial Lagrangian implicitly may be considered as a useful agent to describe a short-ranged, charged and massive interaction.
Keywords: Yukawa potential; Einstein-Maxwell; exact solution; nonlinear electrodynamics